Research on Closed-Loop Control Algorithm of Pneumatic Clutch Based on Optimizing Engaged - Schedule - Li, Xing Zhong; Sun, Shao Hua; Lei, Yu Long (Applied Mechanics and Materials, 2014)
According to the automatic control system of pneumatic AMT clutch, this paper proposes a novel PID control based on logical switch of clutch engagement index. The PWM control is used to make a control for the solenoid valve. And a controller is established by this control algorithm. The automatic control system of pneumatic AMT clutches modeling using the AMEsim software, related simulation analysis and modifying the control parameters of the controller. It is conducted stand test according to the test scheme for the clutch automatic control system. And the test data is record and made an analysis on. The control algorithm is verified by stand test, greatly improving the bonding quality of the clutch.